CENTRALIZATION VS DECENTRALIZATION IN FOREIGN EXCHANGE EXPOSURE MANAGEMENT: A MISPLACED DEBATE? - Mudogo, Ernest (Allied Academies International Conference. Academy of Accounting and Financial Studies. Proceedings, 2003)
Using Beer's viable system model (VSM) in organizational cybernetics, this paper argues that the debate regarding centralization vs decentralization in foreign exchange exposure management (FEEM) is misplaced. The results of interviews on how centralization or decentralization in FEEM is perceived at two organizations suggests that neither extreme is considered suitable. A critical reflection using cybernetic principles indicates that serious focus should be placed upon the need for a flexible FEEM policy that permits local autonomy to all organizational units, subject to accountability for foreign exchange exposure minimization in order to preserve overall organizational cohesiveness and viability. In this paper we seek to make a contribution by providing an explanatory framework within which the centralization vs decentralization debate in managing foreign exchange exposure can be meaningfully interpreted. [PUBLICATION ABSTRACT]